UJI AKTIVIITAS ANTIDIABETES EKSTRAK ETANOL DAUN KELENGKENG VARIETAS KRISTAL (DIMOCARPUS LONGAN L.) TERHADAP MENCIT JANTAN YANG DIINDUKSI ALOKSAN - Pri Hardini (CV. Adiba Aisha Amira, 2024)
Type 2 diabetes mellitus is caused by damage to pancreatic beta cells which results in the inability to produce insulin so that blood sugar levels increase. The purpose of this study was to determine whether the administration of ethanol extract of longan leaves of the crystal variety could reduce blood sugar levels in alloxan-induced mice. The method of this study was experimental using 5 groups of 5 mice each. The doses used were 25, 50, and 100 kg/BB for the positive and negative groups respectively. Data were collected before alloxan induction at 4, 6 and 24 hours after administration of the extract. The results of the study described the presence of flavonoids, tannins and saponins. The most eflective reduction in glucose levels was at a dose of 100 mg/kg BW. The conclusion of the ethanol extract of longan leaves of the crystal variety has the potential as an antidiabetic with an eflective dose of 100 mb/kg BW.